Ulmus davidiana var. japonica Extracts Suppress Lipopolysaccharide-Induced Apoptosis Through Intracellular Calcium Modulation in U937 Macrophages - Yun, Jang-Hyuk; Kim, Hyun-Ouk; Jeong, Jae-Hun; Min, Yerin; Park, Kwang-Hyun; Si, Chuanling; Choi, Sun-Eun (Frontiers in Energy Research, 2022)
This study was conducted to examine the anti-apoptotic effects of Ulmus davidiana extracts by regulation the intracellular cation mobilization in U937 human monocytic cells. To investigate modulatory effects on LPS-induced apoptosis and Ca2+ signaling pathway, we measured intracellular Ca2+ levels and various protein markers such as Bax, Bcl-2 and PARP. To isolate biopotent molecules, branches from U. davidiana were processed sequentially by 60% ethanol, supercritical fluid extraction, and ethyl acetate extraction of the remaining sample to obtain single fractions as well as ultimately catechin-glycoside which is one of the known bioeffector molecules of U. davidiana. LPS increased intracellular Ca2+ mobilization in U937 cells with transient oscillation and markedly increased Bax and PARP protein expression; however Bcl-2 was decreased. Each of the U. davidiana var. extracts as well as catechin-glycoside, significantly reduced LPS-induced intracellular Ca2+ mobilization and apoptosis-related molecules were also downregulated. These results suggest that U. davidiana and catechin-glycoside may be useful for improving immune system function.